Causal Factors Influencing Educational Management Effectiveness of Private Higher Education Institutions in Thailand - Pronsurivong, Nissara; Kawmongkon, Songyos; Saipatthana, Uthaiwan (Interdisciplinary Academic and Research Journal, 2023)
Higher education institutions need to reform themselves along with national reforms that look at all dimensions of development, both in terms of quality and acceptable quality of higher education output, and a driving mechanism in the higher education system that will create quality in administration, create good governance, create a network of cooperation with all sectors. Including the serious use of digital technology in teaching and management in higher education. This study aimed to (1) study the causal factors influencing the effectiveness of educational management of private higher education institutions in Thailand, (2) develop and test the route models of the causal factors influencing the effectiveness of educational management of private higher education institutions in Thailand, and (3) study direct and indirect causal factors influencing the effectiveness of educational management of private higher education institutions in Thailand. The participants in this study were lecturers and staff who are working at private higher education institutions under the principle of structural equation analysis, and stratified sampling. The sampling was defined by Stratified Sampling which was selected by Multi-Stage Sampling. by Simple Random Sampling to obtain a set number of qualified samples. There were 600 people. The Informative groups included 3 executives of private higher education institutions, 3 educators, and 3 government officials. The total was 9 people selected by Purposive Sampling. The research instruments were questionnaires and interviews. The statistics used to analyze the data were Confirmatory factor analysis: CFA and Structural Equation Modeling, SEM. The results found that (1) the causal factors influencing the effectiveness of educational management of private higher education institutions in Thailand are at a very high level. (2) The development and the test of the causal factors influencing the effectiveness of educational management of private higher education institutions in Thailand were consistent with the empirical data that were at a good criterion (x2 = 245.45, df = 249, x2/df=.986, P-value =.552, RMSEA = 0.000). And (3) the effectiveness of educational management of private higher education institutions in Thailand was influenced directly and indirectly by the change of leadership were statistically significant at the level of.05, and influenced directly by information technology (TEC), operational satisfaction (SAT), organization culture (CUL), and organization atmosphere (CLI) were statistically significant at the level of.05.